Amelioration de la production de ligname a travers la fertilisation minerale en zone de savene de Cote dIvoire - Soro, D.; Dao, D.; Carsky, R.J.; Asiedu, Robert; Assa, A.; Girardin, O. (2003)
Improving yam production by mineral fertilisation in the savanna zone of Cote d'Ivoire. Côte d'Ivoire is the second producer of yam after Nigeria with 2.8 millions tons produced per year. Though its farmers are still looking for ‘'virgin'' soil to increase their yields. Mineral fertilization study led in the savanna zone has as objective to determine the response of local yams to mineral fertilizers. Thus, four local varieties (Bètè bètè, Gnan, Krenglè and Wacrou) are tested with two fertility levels. Dose T1(60 25 65 kg/ha NPK) and dose T2 (T2 = 2 * T1) led to an increase in yield of local yams. Then, while the amount of nitrogen is increased with both dose T1 and T2, potassium decreases with the highest dose (T2). Yield increase varies from 14 % to 71 % according to varieties with dose T1. The pounded yam still has no significant difference with the control. Those are promising results. But more information can be gained by using combinations of elements : NP, NK, PK and NPK.